2010
DOI: 10.1021/nl102135k
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dual Emission in Doped Semiconductor Nanocrystals

Abstract: Colloidal manganese-doped semiconductor nanocrystals have been developed that show pronounced intrinsic high-temperature dual emission. Photoexcitation of these nanocrystals gives rise to strongly temperature dependent luminescence involving two distinct but interconnected emissive excited states of the same doped nanocrystals. The ratio of the two intensities is independent of nonradiative effects. The temperature window over which pronounced dual emission is observed can be tuned by changing the nanocrystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
315
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(332 citation statements)
references
References 30 publications
13
315
1
3
Order By: Relevance
“…This doping strategy was similar to dual-emissive CdS/Mn:ZnS core/shell NCs reported by Cao's group [87]. This result was consistent with those observed in typical dual-emissive Mn-doped ZnCdSe NCs [90]. Therefore, The PL spectrum showed two distinguished peaks, one of which was attributed to Mn-related emissions and the other resulted from gradient Zn-Cu-In-S NCs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This doping strategy was similar to dual-emissive CdS/Mn:ZnS core/shell NCs reported by Cao's group [87]. This result was consistent with those observed in typical dual-emissive Mn-doped ZnCdSe NCs [90]. Therefore, The PL spectrum showed two distinguished peaks, one of which was attributed to Mn-related emissions and the other resulted from gradient Zn-Cu-In-S NCs.…”
Section: Resultssupporting
confidence: 90%
“…For example, dual emissive CdSe/ ZnS/CdSe NCs have been used to produce white light by combination with blue and ultraviolet LEDs [52]. However, the emission wavelength of these dual emissive NCs can only be tuned in a limited spectral range [51][52][53][54][55][56][57][58][59][60], which also limits the tunability of color temperature for the NCs-based WLEDs. Generally, these most widely used color converters are not only highly sensitive to the temperature, but are also restricted, especially the cadmium/lead-based, particularly in view of recent environmental regulations and potential application in the fabrication of WLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the relative intensity of excitonic emission increases with temperature. A discussion of the thermal population mechanisms and its effect on photoluminescence was presented by Beaulac et al 104 and Vlaskin et al 80 The maximum relative sensitivity values reported near room temperature for these QDs are 1.3% K À1 at 318 K (ref. 80) ( Table 2 and Fig.…”
mentioning
confidence: 98%
“…This was first reported by Vlaskin et al in Zn 1Àx Mn x Se-ZnCdSe core-shell QD structures. 80 The solubility of such Mn-doped colloidal semiconductor QDs in water was recently achieved, enabling their use in biophysical applications.…”
mentioning
confidence: 99%
“…Nanocrystalline materials can exhibit interesting optical properties that may vary significantly in comparison with bulk crystals of the same chemical composition and this has attracted a great deal of interest in recent years [1][2][3][4][5]. For example, optical properties of transition metal and rare earth doped wide bandgap nanoparticles have been investigated.…”
Section: Introductionmentioning
confidence: 99%